2022
DOI: 10.3389/fragi.2022.926627
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria in Retinal Pigment Epithelial Aging and Degeneration

Abstract: Retinal pigment epithelial (RPE) cells form a monolayer between the neuroretina and choroid. It has multiple important functions, including acting as outer blood-retina barrier, maintaining the function of neuroretina and photoreceptors, participating in the visual cycle and regulating retinal immune response. Due to high oxidative stress environment, RPE cells are vulnerable to dysfunction, cellular senescence, and cell death, which underlies RPE aging and age-related diseases, including age-related macular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 236 publications
(244 reference statements)
0
28
0
Order By: Relevance
“…In healthy retinal cells, ROS levels remain low as a result of normal cellular metabolism. However, accumulation of ROS caused by oxidative stress can act as an initiator in the pathogenesis of degenerative diseases of the retina [ 4 , 35 ]. In this study, inhibition of cell survival, induction of cytotoxicity, and generation of ROS by H 2 O 2 in ARPE-19 cells were significantly suppressed by pretreatment with phloroglucinol or NAC, a free-radical scavenger used as a positive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy retinal cells, ROS levels remain low as a result of normal cellular metabolism. However, accumulation of ROS caused by oxidative stress can act as an initiator in the pathogenesis of degenerative diseases of the retina [ 4 , 35 ]. In this study, inhibition of cell survival, induction of cytotoxicity, and generation of ROS by H 2 O 2 in ARPE-19 cells were significantly suppressed by pretreatment with phloroglucinol or NAC, a free-radical scavenger used as a positive control.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed the possibility that phloroglucinol could block ROS generation caused by oxidative stress. Many previous studies have shown that DNA damage and apoptosis can be induced in RPE cells exposed to oxidative stimuli [ 35 , 36 ]. This finding was also confirmed in H 2 O 2 -treated ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal absorption of ultraviolet rays causes photochemical damage to mitochondria in the RPE, leading to increased ROS generation [ 235 , 236 ]. Specifically, blue light has been associated with significant photooxidative stress and ROS generation [ 237 , 238 ].…”
Section: Retinamentioning
confidence: 99%
“…Dysfunction of mitochondria is a signal indicating cellular senescence, and mitochondrial injury finally results in RPE cell death and degenerative retinal disease [ 90 ]. Both aging and hyperglycemia can lead to oxidative stress, damaging mitochondria and accelerating AMD and RD development [ 91 ]. In glaucoma, mitochondrial dysfunction is accompanied with retinal ganglion cell (RGC) degeneration [ 92 ], which is difficult to repair.…”
Section: Strategies For Treating the Retinal Diseases With Mesenchyma...mentioning
confidence: 99%